2020
DOI: 10.1186/s41983-020-00220-0
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge about Alzheimer disease in Mecca Region, Kingdom of Saudi Arabia: a cross-sectional study

Abstract: Background: Raising the general population knowledge of Alzheimer's disease is crucial for optimizing care and ultimately enhancing the quality of life of people diagnosed and their caregivers. Aim: To assess knowledge among the general population in Makkah Region about symptoms, diagnosis, causes, course, life impact, care giving, and management of Alzheimer disease. Material and methods: A descriptive cross-sectional study was conducted during July to August 2018 in three main cities of Makkah Region, i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
0
2
0
3
Order By: Relevance
“…Another study conducted on general population of Makkah; Saudi Arabia revealed a moderate level of knowledge. However, the study revealed that having a relative with AD was not associated with an increased knowledge level regarding AD (Alhumaidi et al, 2020).…”
Section: Medical Science L Analysis Articlementioning
confidence: 65%
See 1 more Smart Citation
“…Another study conducted on general population of Makkah; Saudi Arabia revealed a moderate level of knowledge. However, the study revealed that having a relative with AD was not associated with an increased knowledge level regarding AD (Alhumaidi et al, 2020).…”
Section: Medical Science L Analysis Articlementioning
confidence: 65%
“…As well as behavioral changes and eventually a decrease in the ability to do the simplest tasks (Ballard et al, 2011;Breijyeh & Karaman, 2020;Studart Neto & Nitrini, 2016). Alzheimer's disease is a rising health problem, with an estimated 6.4% in Saudi Arabia (al Arifi, 2020) and it has been linked with many risks' factors that contribute to the development and progression of disease such as aging, genetic defects, infections, vascular diseases and environmental factors (Alhumaidi et al, 2020;Breijyeh & Karaman, 2020). AD is most prevalent in individuals aged 60 years and most cases of Alzheimer's disease are sporadic.…”
Section: Medical Science L Analysis Articlementioning
confidence: 99%
“…Penyakit alzheimer yang paling sering adalah demensia yang ditandai dengan hilangnya fungsi kognitif, berpikir, mengingat, menalar dan kemampuan perilaku untuk melakukan aktivitas atau kegiatan dasar sehingga dapat mengganggu kehidupan sehari-hari seseorang. Sebagian besar kasus alzheimer terjadi setelah usia 60 tahun dan hampir 3% kasus pada pria dan wanita terjadi pada usia 65 -74 tahun (Alhumaidi et al, 2020).…”
Section: Pendahuluanunclassified
“…Penderita alzheimer secara khas akan menunjukkan gejala gangguan memori dan kemampuan pengambilan keputusan serta masalah lainnya seperti perilaku dan kemampuan verbal mereka. Masalah lainnya yang dihadapi oleh penderita alzheimer antara lain jatuh, kehilangan martabat dan rasa hormat, pelecehan, penelantaran serta eksploitasi (Alhumaidi et al, 2020). Setiap tahun insiden alzheimer di seluruh dunia mengalami peningkatan dengan cepat.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation